“Possibilities of early prevention of chronic kidney disease in patients with type 2 diabetes mellitus based on clinical and anamnestic data” - Kholikov A.Yu; Begmatov B.B; Urmanova Yu.M; Narziev V.Sh (Zien Journals, 2024)
to study the possibilities of early prevention of CKD in patients with type 2 diabetes based on clinical and anamnestic data.
Keywords: anamnestic; possibilities; CKD